Dysplasia epiphysealis hemimelica: A histological comparative study with osteochondromas. (June 2017) - Stevens, J.; Welting, T. J. M.; Witlox, A. M.; van Rhijn, L. W.; Staal, H. M.
Purpose: Dysplasia epiphysealis hemimelica (DEH) is a rare developmental disorder resulting in epiphyseal overgrowth. Based on histological appearance, it is often described as an osteochondroma or osteochondroma-like lesion, although clinical differences exist between DEH and osteochondromas. The aim of this study was to test whether DEH and osteochondromas are histologically identical diseases. Methods: Tissue samples of two age- and gender-matched cases with DEH and hereditary multiple exostoses were histologically compared. Sections were stained with Safranin-O for detection of proteoglycans and immunohistochemistry was performed for detection of collagen type II, collagen type X as a marker of hypertrophic chondrocytes and Sox9 as a marker of proliferative chondrocytes. Due to the rarity, descriptions of the included DEH patients were outlined. Results: Histologically, chondrocyte clusters in a fibrillary matrix, a thick disorganised cartilage cap and ossification centres with small amounts of unabsorbed cartilage, were observed in DEH. In contrast, cartilage organisation of osteochondromas displays characteristics of the normal growth plate. Collagen type II was clearly detected in the cartilaginous extracellular matrix in osteochondromas, while weak expression was observed in DEH. Collagen type X was not detected in DEH, while expressed in the matrix surrounding hypertrophic chondrocytes in osteochondromas. Sox9 staining was positive in hypertrophic chondrocytes in osteochondromas, while expressed in nuclei of chondrocyte clusters in DEH. Conclusion: Both morphological and immunohistological differences were observed in histological sections of DEH and osteochondromas. These results support the previously identified clinical, radiological and genetic differences and imply a different aetiology between DEH and osteochondroma formation.